Relasi Kuasa Ekonomi Global Di Balik Tradisi Perang Tipat Bantal Desa Adat Kapal - Dana Prawira, Komang Bagus; Azhar, Muh. Ali; Pramana, Gede Indra (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2020)
This 0 study 0 aims 0 to 0 determine 0 how the global economic power relations that work behind the tradition of the Perang Tipat Bantal in the Kapal Traditional. Furthermore, the research is framed using Antonio Gramsci's theory of hegemony. The 0 research 0 method used 0 is 0 a 0 descriptive qualitative 0 method using primary data and secondary data, because it describes and describes the global economic power relations that work behind the tradition of the Perang Tipat Bantal. The 0 results 0 of 0 the 0 research are: first, the existing hegemony has transformed this tradition into a tourism object that has an economic impact. Second, from the power relations and political economy of the Perang Tipat Bantal, it shows a conclusive form related to the relationship between economy and politics in a tradition where this tradition is also used as a political stage by political actors. This indicates that this tradition can be transformed into a political stage.   Keywords : Perang tipat Bantal, Politics Tourism Culture, Authenticity